Kopi Cap Gantang: coffee product - Mohd Rosdi, Muhammad Fakhrul Razi (Universiti Teknologi MARA, Perak, 2023)
Kopi Cap Gantang Produce by Gantang Coffee Enterprise SDN. BHD. is located in Baling. Kedah has had experience in producing the coffee powder since 1990. Representing the Malaysia SME Product, Kopi Cap Gantang produces the quality product with aromatic taste of coffee. Even though Kopi Cap Gantang produces quality Malaysian product, unfortunately, it still cannot win the Malaysian consumers' hearts because this product is relatively uknown. Compared to its competitors, there is no gap in production.